Checklist of the freshwater snails (Mollusca: Gastropoda) of Mongolia - Vinarski, Maxim V.; Palatov, Dmitry M.; Marinskiy, Vadim V. (Zootaxa, 2017)
The paper is the first illustrated check-list of the freshwater Gastropoda of the state of Mongolia. The authors examined their own samplings made in 2009–2012 as well as collections of other explorers and zoological museums (mostly those of Russia). In total, 35 nominal species of four families (Valvatidae, Lymnaeidae, Physidae, and Planorbidae) have been included into annotated list, with remarks on their distribution, ecology, taxonomic status, and nomenclature. All species are illustrated by pictures of their shells (including some type specimens). The fauna of freshwater Gastropoda of Mongolia is taxonomically impoverished as compared to the fauna of southern Siberia and other adjacent areas. In particular, no representatives of such families as Acroloxidae and Bithyniidae were found to live there as well as no species of Anisus, Aplexa, Planorbarius, Planorbis, Stagnicola and some other genera of aquatic snails broadly distributed in Palearctic. From the zoogeographic point of view, the recent fauna of aquatic Gastropoda of Mongolia consists of species belonging to three diversification centers—northwestern Palearctic, Siberian, and Central-South Asian. The only species endemic to Mongolia is Choanomphalus mongolicus inhabiting the Hövsgöl Lake. A brief history of formation of the recent Mongolian fauna of freshwater snails is provided.